Ethno-Cultural Factors of Demand for Alternative Practices in the Field of Physical and Mental Health - N.A. Antonova; K.Y. Eritsyan (Moscow State University of Psychology and Education, 2023)
Objective. Study aims to investigate the ethno-cultural factors of demand for alternative practices in the sphere of health and psychological well-being among Russian youth. Background. The decision to seek help is critical to the health and psychological well-being of the individual and society. Turning to non-conventional practices (psychic, paranormal, etc.) to solve problems in the field of both physical and mental health and psychological well-being can be associated with potential risks. Study design. Quantitative cross-sectional study of adolescents and youth in several Russian regions: Saint-Petersburg and Leningradskaya region, Irkutsk, Murmansk and Tomsk regions, Kamchatka and Krasnoyarsk regions, the Republic of Sakha (Yakutia). Data collection was carried out in the form of an online survey in November-December 2020. Participants. The study sample consisted of 1258 adolescents and young people aged 14 years and older, of which 671 are adolescents and young people who identify themselves as indigenous peoples of the North, Siberia and the Far East of the Russian Federation. Young men constituted 33% of the sample, mean age – 22,1 years ( min = 14, max = 35; SD = 6,26). Measurements. The several scales for assessing the help-seeking and related attitudes towards alternative practices, self-assessment of mental health (HBSC scale). Descriptive statistics, contingency tables to assess differences by ethnicity and gender and a logistic regression model predicting intention to future use of the services were calculated. Results. Young people's appeal to providers of alternative practices of help (magicians, fortune-tellers, psychics, etc.) has no ethno-cultural specifics. The youth of the indigenous peoples of the North, Siberia and the Far East significantly more often than the youth of another ethnicity turn only to shamans, who are part of the unique spiritual culture of these ethnic groups but not to any other group of practitioners. Conclusions. Asking for help from different representatives of ...